BSCI-07. BONE MARROW T-CELL SEQUESTRATION IN THE SETTING OF BRAIN METASTASES. (12th August 2019) - Chongsathidkiet, Pakawat; Woroniecka, Karolina; Dechant, Cosette; Kemeny, Hanna; Cui, Xiuyu; Wilkinson, Daniel; Lorrey, Selena; Fecci, Peter
Abstract: INTRODUCTION: Brain metastases remain one of the most dreaded consequences of late stage cancer, yet their incidence has risen as survival from primary cancers has improved. We have recently reported that tumors harbored within the brain, specifically, sequester T-cells within the bone marrow as a novel mechanism of immune evasion. Sequestration results from tumor-imposed loss of S1P1 receptor from the T-cell surface. Stabilization of the receptor on T-cells frees T-cells from sequestration and licenses T-cell activating therapies for intracranial tumors. While this phenomenon was initially uncovered in glioblastoma, its role in promoting immune-evasion in brain metastases remains less clear. METHODS: Blood, bone marrow, and tumors were collected from mice bearing intracranial tumors commonly metastatic to the brain, including lung carcinoma (LLC), melanoma (B16F10), or breast carcinoma (E0771) and analyzed by flow cytometry. T-cell S1P1 levels, as well as total T-cell counts were assessed in each compartment. Correlation analyses were conducted between T-cell counts and S1P1 levels on T-cells in the bone marrow across intracranial and subcutaneous murine tumor models. RESULTS: T-cell lymphopenia and accompanying accumulation of T-cells in the bone marrow were observed in the murine models of lung carcinoma, melanoma, and breast carcinoma, but only when these tumor lines were implanted intracranially. Sequestered T-cells in tumor-bearing mice showed decreased surface S1P1 levels in a manner correlating with their sequestration. CONCLUSION: S1P1-mediated bone marrow T-cell sequestration is a novel mode of cancer-induced T-cell dysfunction in intracranial tumors. Preventing receptor internalization abrogates T-cell sequestration and licenses T-cell activating therapies in glioblastoma. Sequestration is now observed in models of brain metastases. Pharmacologic strategies to stabilize S1P1, reverse sequestration, and restore circulating T-cell numbers are anticipated to improve immunotherapeutic efficacy for brain metastases.